Musculoskeletal disorders: Epidemiology and treatment seeking behavior of secondary school students in a Nigerian community - Adegbehingbe Olayinka; Fatusi Adesegun; Adegbenro Caleb; Adeitan Opeyemi; Abass Ganiyu; Akintunde Akintomiwa (Wolters Kluwer Medknow Publications, 2009)
Background: Epidemiological information paucity exists on musculoskeletal disorders (MSD) among secondary school students in Nigeria. We aimed to determine the prevalence, pattern, and treatment seeking behaviors (TSB) of MSD in Southwest, Nigeria. Materials and Methods: A school-based cross-sectional study was conducted in four randomly selected secondary schools in Ile-Ife in 2007. All the students were screened for MSD using an interviewer-administered questionnaire and physical examination, which involved the use of a scoliometer and a goniometer. Affected children were recommended for follow-up treatment and a plain radiography taken. Results: A total of 133 students had 204 MSD representing a 3.0% prevalence among the 4,441students screened. Eighty-one (60.9%) students had congenital disorders and 52 (39.1%) were acquired. The lower limbs (93.1%) were most commonly affected and 87 (65.4%) students presented with a knee deformity. Other abnormalities were limb length discrepancy 6.8%, scoliosis 4.4%, Pes planus 3.9%, and poliomyelitis 2.9%. A total of 100 students (75.2%) had no form of treatment, 18.8% receive treatment in the hospital, 3.7% received treatment in a traditional healing home and 2.3% received treatment in a church. Age, family, and school type were significant factors ( P < 0.05) in health-seeking behavior. The factors affecting treatment outcome were the place of treatment, hospital specific treatment, and reasons for stopping treatment. Conclusion: Treatable cases constitute a large proportion of MSD among secondary school students, but TSB was generally poor. Parental socio-economic and health services factors were related to the health-seeking behavior. Strengthening of school health services and improved linkage with orthopedic services, community education on MSD, and education of all cadres of health professionals are recommended.